Genome Copy Number Quantification Revealed That the Ethanologenic Alpha-Proteobacterium Zymomonas mobilis Is Polyploid - Fuchino, Katsuya; Wasser, Daniel; Soppa, Jörg (Frontiers in Microbiology, 2021)
The alpha-proteobacterium Zymomonas mobilis is a promising biofuel producer, based on its native metabolism that efficiently converts sugars to ethanol. Therefore, it has a high potential for industrial-scale biofuel production. Two previous studies suggested that Z. mobilis strain Zm4 might not be monoploid. However, a systematic analysis of the genome copy number is still missing, in spite of the high potential importance of Z. mobilis. To get a deep insight into the ploidy level of Z. mobilis and its regulation, the genome copy numbers of three strains were quantified. The analyses revealed that, during anaerobic growth, the lab strain Zm6, the Zm6 type strain obtained from DSMZ (German Collection of Microorganisms), and the lab strain Zm4, have copy numbers of 18.9, 22.3 and 16.2, respectively, of an origin-adjacent region. The copy numbers of a terminus-adjacent region were somewhat lower with 9.3, 15.8 and 12.9, respectively. The values were similar throughout the growth curves, and they were only slightly downregulated in late stationary phase. During aerobic growth, the copy numbers of the lab strain Zm6 were much higher with around 40 origin-adjacent copies and 17 terminus-adjacent copies. However, the cells were larger during aerobic growth, and the copy numbers per µm3 cell volume were rather similar. Taken together, this first systematic analysis revealed that Z. mobilis is polyploid under regular laboratory growth conditions. The copy number is constant during growth, in contrast to many other polyploid bacteria. This knowledge should be considered in further engineering of the strain for industrial applications.